Operational Risk Management Design In The Indonesia Mining Growth Program (P3I) Using House Of Risk Method - Mangasa Siregar; Suparno Suparno (IPTEK Journal of Proceedings Series, 2020)
The Indonesia Mining Growth Program (P3I) is a development project activity for nickel Mining Enterprise and Processing Plant in the "X" Region in Sulawesi. This research will design a risk management framework for P3I by implementing Enterprise Risk Management (ERM). In this study, the method is used to analyze the potential operational risks that exist in P3I namely the House of Risk (HOR) model. The results of the identification of risk events in the operational business processes of P3I found 25 risk events divided into each business process, namely 8 risk events in the mine planning process, 7 risk events in the design implementation process, 8 risk events in the production process, 1 risk event in the product delivery process and 1 risk event in the process of returning waste from Processing Plant. Thus, the results of the identification of risk triggers (risk agents) found 23 risk causes (risk agents). The result of the Aggregate Risk Potential (ARP) recapitulation is an output calculation based on the HOR model phase 1, there are 7 top-ranked risk agents since it is considered to be able to hamper the company's goals. Thus, in determining the preventive actions, 17 preventive actions were obtained, which were then put into the HOR phase 2 model to rank the most effective prevention measures based on cost and resources.